Offshore Platform Integration and Floatover Technology - Liu, Gengshen; Li, Huajun; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book discusses offshore platform integration technology, focusing on the floatover methodology and its applications. It also addresses topics related to safety and cost-effectiveness, as well as ensuring the success of a project through careful planning and established detailed operation procedure/working manuals, which are rarely found in the published literature. Unlike other publications in this area, the book not only includes details of technology development, but also presents real project cases in the discussion to make it more comprehensible. Each topic is illustrated with carefully created sketches to show the complex operation procedures. .
Offshore Platform Topsides and Substructure -- Platform Integration and Stationing -- Floatover Technology -- Hideck Floatover Technology -- Unideck & Smartleg -- Catamaran Floatover -- Project Management & Planning -- Engineering Analysis and Model Test -- Operation Execution -- Evolution and New Source of Motivation.
Keywords: Offshore structures; Construction industry -- Management; Mechanics, Applied; Solids; Buildings -- Design and construction; Offshore Engineering; Construction Management; Solid Mechanics; Building Construction and Design